ANALYSIS OF MEASUREMENT OF SUSTAINABLE DEVELOPMENT IN THE INSURANCE COMPANY - Indre Lapinskaite; Giedre Radikaite (European Scientific Journal, ESJ, 2015)
There are a number of different ways how to measure the company’s performance on sustainable development; despite it is not easy task to identify and choose which method is more accurate and appropriate, researches have shown that framing sustainability performance with methods of measurement can bring clearness into accountancy and significantly increase a company’s performance. The object of the research is the biggest insurance company in Lithuania and the Baltic countries. In this paper the key methods of sustainability indexes and sustainability indicator systems that are used in a level of company are analysed. To find out how the results of two measurement methods for company’s sustainable development might differ, while measuring the same company, the expert analysis was used. The analysis of sustainability measurements of company’s performance on sustainable development shows that there is likely to be different possible outcomes if company is being analysed by two, or more, different measurement methods.